Alegorija petih čutov na freskah v gradu Jablje in na slikanih tapetah iz gradov Dornava in Zaprice - Murovec, Barbara (Zbornik za umetnostno zgodovino (Nova vrsta), 1993)
The article presents graphic models and iconographic sources of the frescoes at the castle of Jablje and the painted wall coverigs from Dornava and Zaprice. The allegories of the Five senses represented in these three Slovenian painted series where modelled on graphic prints by Gottfried Bernhard Götz. The Dornava painted wallcoverings, for which the graphic models have been established with certainty, were painted by combining individual figures and compositions from Götz's prints as well as prints modelled on paintings by the French Rococo painter Nicolas Lancret.
Keywords: Slovenia; Slovenija; gradovi; art of painting; slikarstvo; freske; 18.st.; Jablje; Dornava; Zaprice